2015
DOI: 10.1007/s12253-015-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toll-Like Receptors 2/3/4/9 Gene Polymorphisms in Cervical Cancer Evolution

Abstract: Accumulative epidemiological evidence suggests that polymorphisms of Toll-like receptors signaling pathway elucidated the cellular and molecular mechanisms of human diseases whose gaining a primordial importance. The aim of our study is to identify the role of TLR 2 (-196 to -174 del), TLR 3 (1377 C>T), TLR 4 (Asp299Gly) and TLR 9 (G2848A) gene polymorphisms with the evolution of cervical cancer in Tunisian women. Blood samples were collected from histopathologically confirmed patients with cervical cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…evaluated the role of TLR2 in periodontal disease in an HIV positive North American cohort and found it to be associated with bleeding on probing, an indicator of an subgingival inflammatory response to bacterial pathogens. The results of the present study are also consistent with previous studies conducted in Indian and other Asian population showing that the TLR2 Ins/Del polymorphism is associated with the risk of severe malaria, cervical cancer, gallbladder cancer, prostate cancer, Epstein–Barr virus associated gastric carcinoma in Chinese and tuberculosis …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…evaluated the role of TLR2 in periodontal disease in an HIV positive North American cohort and found it to be associated with bleeding on probing, an indicator of an subgingival inflammatory response to bacterial pathogens. The results of the present study are also consistent with previous studies conducted in Indian and other Asian population showing that the TLR2 Ins/Del polymorphism is associated with the risk of severe malaria, cervical cancer, gallbladder cancer, prostate cancer, Epstein–Barr virus associated gastric carcinoma in Chinese and tuberculosis …”
Section: Discussionsupporting
confidence: 92%
“…29 It was also found to be associated with tuberculosis in Caucasians and Africans, 30 colorectal cancer in Brazilians, 31 in breast cancer 32 and in Parkinson 0 s disease in a Greek population. 33 Asian population showing that the TLR2 Ins/Del polymorphism is associated with the risk of severe malaria, 35 cervical cancer, 36,37 gallbladder cancer, 38 prostate cancer, 17,39 Epstein-Barr virus associated gastric carcinoma in Chinese 40,41 and tuberculosis. 42 The three nonsynonymous polymorphisms in the TLR2 gene (Arg753Gyn, Arg677Trp and Pro631His) are associated with altered TLR2 signaling and have been reported to influence susceptibility to various infections.…”
Section: Discussionmentioning
confidence: 99%
“…The results of pooled analysis for TLR2 polymorphism and cancer susceptibility are provided in Table 2 . For -196 to -174del, we collected 18 articles containing 3943 cases and 4574 controls [1][2][3]6,[8][9][10][11][12][28][29][30][31][32][33][34][35][36]. In the overall analysis, -196 to -174del significantly increased the risk of cancer [B vs. A (OR = 1.468, 95% Cl = 1.129-1.91, P=0.005); BB vs. AA (OR = 1.716, 95% Cl = 1.178-2.5, P=0.005); BA vs. AA (OR = 1.408, 95% Cl = 1.092-1.816, P=0.008); BB+BA vs. AA (OR = 1.449, 95% Cl = 1.107-1.897, P=0.007); BB vs. BA+AA (OR = 1.517, 95% Cl = 1.092-2.107, P=0.013)] ( Figure 2).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Otherwise, investigation of TLR3 rs5743305 and rs3775291 polymorphisms has shown no significant correlation between these SNPs and the risk of cervical cancer, among a Swedish population [49]. Among North Indian population, Pandey et al found no association between rs3775290 TLR3 polymorphism and cervical cancer development [50], while Zidi et al found that rs3775290 TLR3 polymorphism (+1377 C > T genotype) increased the risk of cervical cancer in advantage stages [40].…”
Section: • Association Between Tlr2 and Cancermentioning
confidence: 99%